(untitled) - Bjonander, Stefan (Birmingham, U.K., 2008)
Includes index
Keywords: Microsoft Visual C++.; C++ (Computer program language); Application software -- Development; C++ (Ngôn ngữ lập trình máy tính); Phần mềm ứng dụng -- Phát triển